1972
DOI: 10.3758/bf03206261
|View full text |Cite
|
Sign up to set email alerts
|

Types and frequency of errors in visual search

Abstract: The experimental method allowed false-positive as weIl as false-negative errors to be measured during visual search. Data were collected from eight Ss on four target-set size conditions on each of 25 days in order to determine whether the finding that search rate is independent of target-set size after practice might be attributable to a systematic variation in total error rate with set size. Even after practice, these Ss continued to search significantly faster for a single target than for target sets which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Although this procedure was employed in other studies which have shown an overall effect, these studies have also shown how the effect can be obscured. For example, Kristofferson (1972) reported that search times with an intermediate level of target uncertainty (N = 5) were no different from those obtained with maximum target uncertainty (N = lo), while Gould and Carn (1973) found search times to be longer with an intermediate level than with maximum target uncertainty.…”
Section: Disciissiortmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this procedure was employed in other studies which have shown an overall effect, these studies have also shown how the effect can be obscured. For example, Kristofferson (1972) reported that search times with an intermediate level of target uncertainty (N = 5) were no different from those obtained with maximum target uncertainty (N = lo), while Gould and Carn (1973) found search times to be longer with an intermediate level than with maximum target uncertainty.…”
Section: Disciissiortmentioning
confidence: 99%
“…For example. Kristofferson (1972) reported that even after 25 days of practice search times were 30% longer with N = 5 than with N = 1. Gould and Cam (1973) reported a 25% increase forN = 10 overN = 1 after 10 days of practice, and Monk's (1976) results showed an overall increase of 10% as N was raised from 1 to 4. .…”
Section: Disciissiortmentioning
confidence: 99%
See 1 more Smart Citation
“…When a low error criterion is imposed on the above set of conditions, the search function is altered (Kristofferson, 1972b: Wattenbarger, 1968. The search function is negatively accelerated throughout practice.…”
mentioning
confidence: 99%
“…A. ROBERTSON Manchester Polytechnic,Manchester,England Mi5 5FG Stimulus materials for visual search experimentation of the sort performed by Neisser (1963) and later by Kristofferson (1972) often take the form of lists of, or matrices containing a number of background elements and a number of targets. In this context, elements and targets might well be numbers, letters, words, or other characters or character strings.…”
mentioning
confidence: 99%